Prospective evaluation of protein bound vitamin B12(cobalamin) malabsorption in the elderly using trout flesh labelled in vivo with 57Co-cobalamin. Issue 4 (1st October 1997) - Aimone-Gastin, I; Pierson, H; Jeandel, C; Bronowicki, J P; Plénat, F; Lambert, D; Nabet-Belleville, F; Guéant, J L
Abstract : Background —The frequency of dietary protein bound vitamin B12 malabsorption in elderly patients remains controversial. Aims —To evaluate this malabsorption in elderly hospitalised patients using a modified Schilling test. Patients —Fourteen elderly patients with low B12 blood levels were prospectively selected from 394 hospitalised patients. Methods —The modified Schilling test was performed with trout labelled in vivo. Results —The test was normal in five healthy elderly subjects, in 7/8 patients with pancreatic insufficiency, and in nine non-elderly patients with antral gastritis. The low decision limit was established at 3.3% (median 4.8%). From the 14 elderly patients with low B12 prospectively selected from 394 hospitalised patients, seven had a real deficiency with anaemia and an increased homocysteine and/or methylmalonate serum level. The modified Schilling test showed malabsorption in five of these patients, including two in which the standard Schilling test was normal, and three in which the standard Schilling test was partially corrected by an intrinsic factor. Conclusions —Protein bound vitamin B12 malabsorption was detected in at least 0.5% of elderly hospitalised patients, using the labelled trout flesh absorption test.